Determination of Critical Nitrogen Dilution Curve Based on Stem Dry Matter in Rice - Ata-Ul-Karim, Syed Tahir (Public Library of Science, 2014)
Plant analysis is a very promising diagnostic tool for assessment of crop nitrogen (N) requirements in perspectives of cost effective and environment friendly agriculture. Diagnosing N nutritional status of rice crop through plant analysis will give insights into optimizing N requirements of future crops. The present study was aimed to develop a new methodology for determining the critical nitrogen (N(c)) dilution curve based on stem dry matter (S(DM)) and to assess its suitability to estimate the level of N nutrition for rice (Oryza sativa L.) in east China. Three field experiments with varied N rates (0–360 kg N ha(−1)) using three Japonica rice hybrids, Lingxiangyou-18, Wuxiangjing-14 and Wuyunjing were conducted in Jiangsu province of east China. S(DM) and stem N concentration (SNC) were determined during vegetative stage for growth analysis. A N(c) dilution curve based on S(DM) was described by the equation (N(c) = 2.17W(−0.27)with W being S(DM) in t ha(−1)), when S(DM) ranged from 0.88 to 7.94 t ha(−1). However, for S(DM) < 0.88 t ha(−1), the constant critical value N(c) = 1.76% S(DM) was applied. The curve was dually validated for N-limiting and non-N-limiting growth conditions. The N nutrition index (NNI) and accumulated N deficit (N(and)) of stem ranged from 0.57 to 1.06 and 51.1 to −7.07 kg N ha(−1), respectively, during key growth stages under varied N rates in 2010 and 2011. The values of ΔN derived from either NNI or N(and) could be used as references for N dressing management during rice growth. Our results demonstrated that the present curve well differentiated the conditions of limiting and non-limiting N nutrition in rice crop. The S(DM) based N(c) dilution curve can be adopted as an alternate and novel approach for evaluating plant N status to support N fertilization decision during the vegetative growth of Japonica rice in east China.